Reversions of QuantiFERON-TB Gold Plus in tuberculosis contact investigation: A prospective multicentre cohort study - Sandra Pérez-Recio; Maria D. Grijota-Camino; Luis Anibarro; Ramón Rabuñal-Rey; Josefina Sabria; Paloma Gijón-Vidaurreta; Virginia Pomar; Mercedes García-Gasalla; Ángel Domínguez-Castellano; Matilde Trigo; María Jesús Santos; Alba Cebollero; et al. (PLoS ONE, 2023)
Background Interferon-y Release Assays (IGRA) reversions have been reported in different clinical scenarios for the diagnosis of tuberculosis (TB) infection. This study aimed to determine the rate of QuantiFERON-TB Gold Plus (QFT-Plus) reversions during contact investigation as a potential strategy to reduce the number of preventive treatments. Methods Prospective, multicentre cohort study of immunocompetent adult contacts of patients with pulmonary TB tested with QFT-Plus. Contacts with an initial positive QFT-Plus (QFT-i) underwent a second test within 4 weeks (QFT-1), and if negative, underwent a repeat test 4 weeks later (QFT-2). Based on the QFT-2 result, we classified cases as sustained reversion if they remained negative and as temporary reversion if they turned positive. Results We included 415 contacts, of whom 96 (23.1%) had an initial positive test (QFT-i). Following this, 10 had negative QFT-1 results and 4 (4.2%) of these persisted with a negative result in the QFT-2 (sustained reversions). All four sustained reversions occurred in contacts with IFN-γ concentrations between ≥0.35 and ≤0.99 IU•mL-1 in one or both QFT-i tubes. Conclusion In this study, TB contact investigations rarely reveal QFT-Plus reversion. These results do not support retesting cases with an initial positive result to reduce the number of preventive treatments.